Food intake and nutritional status of hospitalised older people - De Oliveira, Maria Rita Marques [UNESP]; Leandro-Merhi, Vânia Aparecida (Wiley, 2011)
Background and aims. Disease is influenced by the nutritional status of the individual. We have assessed the relationship between nutritional status and food intake among recently hospitalised older people. Methods. A cross-sectional study was undertaken with 240 older people in a hospital that provides care for the public and private healthcare systems. Nutritional status was classified by the MNA (Mini Nutritional Assessment) into: malnourished, risk of malnutrition and without malnutrition. Food intake was estimated by the reported food intake during a typical day. The Kruskal-Wallis test was used to compare the medians and the correlation coefficient of Spearman to verify the relationship between the consumption of energy, protein and vitamin C and MNA scores. Results. 33.8% were classified as adequate regarding nutritional status; 37.1% were classified as being at risk of malnutrition and 29.1% were classified as malnourished. The malnourished individuals reported significantly less energy and nutrient intake than those at risk of malnutrition or those without malnutrition (P=0.001). Not all nutrient intake, just some (iron, cholesterol and fibre), were lower in malnourished people. Conclusions and implications for practice. Deterioration of the nutritional status of older people is accompanied by a reduction in energy and some nutrient intake. The investigation of food intake in older people could provide important information about nutritional risk. © 2010 Blackwell Publishing Ltd.
Keywords: Food intake; Nutritional status; Older people; aged; Brazil; caloric intake; cross-sectional study; female; general hospital; geriatric assessment; hospital patient; hospitalization; human; male; malnutrition; middle aged; nutritional assessment; nutritional status; prevalence; psychological aspect; risk factor; sex ratio; statistics; urban population; Aged; Cross-Sectional Studies; Energy Intake; Female; Geriatric Assessment; Hospitalization; Hospitals, General; Humans; Inpatients; Male; Malnutrition; Middle Aged; Nutrition Assessment; Nutritional Status; Prevalence; Risk Factors; Sex Distribution; Urban Population